Design and software implementation of radio frequency satellite link based on SDR under noisy channels - Ahmed A. Thabit (Universitas Ahmad Dahlan, 2020)
The satellite communication providea utilization of radio frequency links. Specific frequencies are dedicated for satellite correspondences through global administrative and coordination procedures which keeps impedance amongframeworks. Over typical work, the satellite receives uplinked indicator fromearth. Progressions its frequency marginally will keep away from self-intervention then re-transmits signal ahead the downlink on the land. Pathloss depicts characteristic Propagate outside the sending signal front as it goes bythe space. A software defined radio (SDR) is a flexible technology that aimsto replace all hardware by software to enables the design of adaptive communications systems such as changing frequencies, modulation schemes and data rates. Applied to small satellites, some of the implications areincreased data through put when down-linking or up-linking by varying communications parameters and making use of one hardware design and implementation for communicating for many missions, just by updating the software. Therefore, development time for small satellite communication systems can be reduced in the future. This paper analyzes, design and software implementation of radio frequency satellite communications links under noisy channels such as phase/frequency offsets and noise temperature. Modulation schemes such as 64QAM system is used based on Matlab tools to implement the results. Obtained results shows a good response that get the goal from the paper.